NEW STABILITY INDICATING METHOD DEVELOPMENT AND VALIDATION OF CAPECITABINE AND DOCETAXEL IN BULK AND PHARMACEUTICAL DOSAGE FORM BY USING RP-HPLC - TIRUMALASETTY, NEEHARIKA; D., RAMCHANDRAN (International Journal of Applied Pharmaceutics, 2021)
Objective: The current investigation was pointed at developing and progressively validating novel, simple, responsive and stable RP-HPLC method for the measurement of active pharmaceutical ingredients of Capecitabine and Docetaxel. Methods: A simple, selective, validated and well-defined stability that shows gradient RP-HPLC methodology for the quantitative determination of Capecitabine and Docetaxel. The chromatographic strategy utilized Inertsil ODS column of dimensions 250x4.6 mm, 5 micron, using isocratic elution with a mobile phase of acetonitrile and water (50:50). A flow rate of 1 ml/min and a detector wavelength of 220 nm utilizing the PDA detector were given in the instrumental settings. Using the impurity-spiked solution, the chromatographic approach was streamlined. Validation of the proposed method was carried out according to an international conference on harmonization (ICH) guidelines. Results: LOD and LOQ for the two active ingredients and their impurities were established with respect to test concentration. The calibration charts plotted were linear with a regression coefficient of R2>0.999, means the linearity was within the limit. Recovery, specificity, linearity, accuracy, robustness, ruggedness were determined as a part of method validation and the results were found to be within the acceptable range. Conclusion: The proposed method to be fast, simple, feasible and affordable in assay condition. During stability tests, it can be used for routine analysis of production samples and to verify the quality of drug samples during stability studies.